Long-term outcomes in patients with multiple endocrine neoplasia type 1 and pancreaticoduodenal neuroendocrine tumours - Donegan, D.; Singh Ospina, Naykky; Rodríguez Gutiérrez, René; Al Hilli, Zahraa; Thompson, G. B.; Clarke, B. L.; Young, W. F. (Blackwell Scientific Publications, 2016)
Summary Background In patients with multiple endocrine neoplasia type 1 (MEN-1), pancreaticoduodenal (PD) neuroendocrine tumours (NETs) are associated with early mortality, yet the best treatment strategy remains uncertain. Aim To assess patient important outcomes (mortality and metastasis) of PD-NETs and predictors of outcomes in patients with MEN-1. Methods Retrospective cohort of patients with MEN-1 who attended the Mayo Clinic, Rochester, MN from 1997 to 2014. Results We identiﬁed 287 patients with MEN-1; 199 (69%) patients had 217 PD-NETs. Among those with a PD-NETs, 129 (65%) had surgery of which 90 (70%) had their primary surgery performed at Mayo Clinic. The median postoperative follow-up was 8 years during which 13 (14%) patients died. The mean (±standard deviation) age of death was 51 (±9) years. Tumour size, metastasis at surgery or tumour type were not predictive of mortality, but for every year older at surgery, the odds of metastasis increased by 6%. Surgery was not performed in 70 (35%) patients. Among those who were observed/medically managed without known metastatic disease, mean tumour growth was 0·02 cm/year (range, -0·13–0-4 cm/year). Four patients (7%) died at a median age of 77 (range, 51–89) years. Conclusion PD-NETs are common in patients with MEN-1 and are associated with early mortality even after surgical intervention. Active surveillance is a viable option in nonaggressive PD-NETs, although deﬁnitive factors identifying such patients are lacking. Therefore, counselling regarding risks and beneﬁts of current treatment options remains integral to the care of patients with MEN-1.